تقييم مسار مكافحة الفقر في إطار تجسيد برنامج أهداف الألفية الإنمائية للأمم المتحدة حتى عام 2015: دراسة حالة الدولة العربية - عباس، وداد Abbas, Wedad (جامعة محمد لمين دباغين سطيف 2, 2015)
Poverty exceeds the concept of insufficient income to deprivation of nutrition, health care, education, training, adequate housing and economic and political participation. There are about 1.3 billion people in the world suffering from this phenomenon that is why eradication of poverty is the main objective, which the other development goals focus on, as all the countries of the world, seek to place the appropriate policies and programs to reduce poverty and achieve the Millennium Development Goals. The Arab countries, like other developing countries, suffer from the spread of poverty but to varying degrees. Some Arab countries recorded the highest rates with levels of low-income. However, they depend on a range of diverse economic and social policies, in Order to reduce the spread of this phenomenon. Not all these efforts have realized the desired objectives and that is due to the combination of a number of factors.
يتعدى مفهوم الفقر عدم كفاية الدخل، إلى الحرمان من التغذية، والعناية الصحية، والتعليم والتكوين، والسكن اللائق، والمشاركة الاقتصادية والسياسية. يعاني من هذه الظاهرة حوالي 1,3 مليار شخص في العالم، لهذا أصبح القضاء على الفقر الهدف الرئيس الذي تتمحور حوله باقي الأهداف الإنمائية، حيث تسعى كل دول العالم إلى وضع السياسات والبرامج الملائمة للحد من الفقر وتحقيق أهداف الألفية. الدول العربية كغيرها من دول العالم النامي تعاني من انتشار ظاهرة الفقر، لكن بدرجات متفاوتة، حيث تسجل الدول العربية المنخفضة الدخل أعلى المعدلات. غير أنها تعتمد على مجموعة من السياسات المتنوعة، اقتصادية واجتماعية بهدف الحد من انتشار هذه الظاهرة، لكن كل هذه الجهود لم تحقق الأهداف المرجوة ويرجع ذلك لتضافر عدة أسباب.
Keywords: الأمم المتحدة -- التنمية المستدامة -- برنامج الأمم المتحدة الإنمائي -- مكافحة الفقر -- العالم العربي